2014
DOI: 10.1186/s13071-014-0525-3
|View full text |Cite
|
Sign up to set email alerts
|

The speed of kill of fluralaner (Bravecto™) against Ixodes ricinus ticks on dogs

Abstract: BackgroundPathogens that are transmitted by ticks to dogs, such as Anaplasma phagocytophilum, Babesia spp., Borrelia burgdorferi sensu latu, and Ehrlichia canis, are an increasing problem in the world. One method to prevent pathogen transmission to dogs is to kill the ticks before transmission occurs. Fluralaner (Bravecto™) is a novel isoxazoline insecticide and acaricide that provides long persistent antiparasitic activity following systemic administration. This study investigated the speed of kill of flurala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 27 publications
2
24
1
Order By: Relevance
“…As observed by other authors (Taenzler et al, 2014;Wengenmayer et al, 2014;Fourie et al 2015), no side effects were observed in the current study. The drugs normally used to treat generalized demodicosis may have some side effects (Sartor e Santarem, 2006;Singh et al, 2011, Delayte et al, 2006; however, fluralaner treatment was both effective and safe.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As observed by other authors (Taenzler et al, 2014;Wengenmayer et al, 2014;Fourie et al 2015), no side effects were observed in the current study. The drugs normally used to treat generalized demodicosis may have some side effects (Sartor e Santarem, 2006;Singh et al, 2011, Delayte et al, 2006; however, fluralaner treatment was both effective and safe.…”
Section: Discussionsupporting
confidence: 89%
“…Fluralaner belongs to this new class and has prolonged activity against fleas and ticks after a single oral dose (Kilp et al, 2014) of 25 mg/kg, with no adverse effects observed during a safety trial, even at higher doses (Walther et al, 2014). No side effects were observed by the authors of previous studies either (Taenzler et al, 2014;Wengenmayer et al, 2014;Fourie et al, 2015). However, one study reported inappetence, vomiting, and diarrhea (Rohdich et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Isoxazolines, like sarolaner and afoxolaner, have been shown to kill adult ticks and prevent B. burgdorferi transmission in dogs [21,22]. Fluralaner, another member of this new family, is noted for its ability to kill ticks rapidly and for its long efficacy period following a single oral administration, when used in dogs [23,24]. Wengenmayer et al [24] showed that, in dogs, fluralaner (Bravecto TM chewable formulation) killed 98% of infesting adult Ixodes ricinus ticks within 24 hours following a single oral administration up to 12 weeks post-treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Fluralaner (Bravecto) (Fig. 1) is a recently marketed isoxazoline ectoparasiticide that is used for flea and tick protection in pets (Taenzler et al, 2014;Wengenmayer et al, 2014). This compound inhibits agonist responses in both GABACls and GluCls, with selectivity for the former over the latter (Ozoe et al, 2010), whereas IVM is a selective activator or modulator for GluCls (Fuse et al, 2016).…”
Section: Introductionmentioning
confidence: 99%